2020
DOI: 10.3390/jcm9010274
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Genomic Mapping Implicates LRRK2 for Intellectual Disability and Autism at 12q12, and HDHD1, as Well as PNPLA4, for X-Linked Intellectual Disability at Xp22.31

Abstract: We report a genomic and phenotypic delineation for two chromosome regions with candidate genes for syndromic intellectual disability at 12q12 and Xp22.31, segregating independently in one family with four affected members. Fine mapping of three affected members, along with six unreported small informative CNVs, narrowed down the candidate chromosomal interval to one gene LRRK2 at 12q12. Expression studies revealed high levels of LRRK2 transcripts in the whole human brain, cerebral cortex and hippocampus. RT-qP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 97 publications
0
15
0
Order By: Relevance
“…While most members of PNPLA family (PNPLA2, PNPLA3, PNPLA5, and PNPLA7) have their role in lipid storage and metabolism [Fischer et al, 2007;Reilich et al, 2011;Mikhailova et al, 2019;Pingitore and Romeo, 2019;Wang et al, 2020], PNPLA1 is associated with congenital ichthyosis (OMIM #612121). Labonne et al [2020] recently proposed PNPLA4 as likely genes for X-linked in- Our patient harbored a missense variant in the patatin domain of PNPLA8. All 3 previously reported patients had truncating variations that lie outside this domain (Fig.…”
Section: Discussionmentioning
confidence: 71%
“…While most members of PNPLA family (PNPLA2, PNPLA3, PNPLA5, and PNPLA7) have their role in lipid storage and metabolism [Fischer et al, 2007;Reilich et al, 2011;Mikhailova et al, 2019;Pingitore and Romeo, 2019;Wang et al, 2020], PNPLA1 is associated with congenital ichthyosis (OMIM #612121). Labonne et al [2020] recently proposed PNPLA4 as likely genes for X-linked in- Our patient harbored a missense variant in the patatin domain of PNPLA8. All 3 previously reported patients had truncating variations that lie outside this domain (Fig.…”
Section: Discussionmentioning
confidence: 71%
“…Similar to PNPLA3, various enzymatic activities have been attributed to PNPLA4, including TG and retinyl ester hydrolase, phospholipase and transacylase activities 8,225,226 . Genetic analyses have suggested that PNPLA4 is involved in the development of two rare congenital disorders: combined oxidative phosphorylation deficiency (COXPD) and X-linked intellectual disability 227,228 . COXPD arises from a hemizygous nonsense mutation resulting in a C-terminally-truncated protein (R187ter) and defective assembly of complexes I, III and IV of the respiratory electron transport chain.…”
Section: Pnpla Family Membersmentioning
confidence: 99%
“…However, its centrality is low in patient 1 (C B = 7.56 × 10 –3 ), whereas it has the top value in the other three patients. Recently, a role for LRRK2 in cognitive development has been proposed, thus linking LRRK2 to intellectual disability and autism ( Labonne et al, 2020 ). Another gene present with very high centrality in all four networks, ESR1 , has been related to the pathogenesis of autism and autism related symptoms ( Wang et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%